2009
DOI: 10.1590/s0100-40422009000800008
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoids from Azorella trifurcata (Gaertn.) Pers and their effect against the enzyme acetylcholinesterase

Abstract: Recebido em 15/7/08; aceito em 4/5/09; publicado na web 6/10/09The inhibition of the enzyme acetylcholinesterase is considered as a strategy for the treatment of Alzheimer's disease, senile dementia, ataxia, and myasthenia gravis. Three lanostane-and two cycloartane-type triterpenes, together with two mulinane-type diterpenes were isolated from petroleum ether extract of the whole shrub of Azorella trifurcata (Gaertn.) Pers. Their effect on the enzyme acetylcholinesterase was assessed as well. In addition, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
(21 reference statements)
0
17
0
Order By: Relevance
“…Table 1 and 2. An interesting group of bioactive metabolites, such as triterpenoids and diterpenoids with azorellane and mulinane skeletons have been obtained from Azorella, and Mulinum genera (Borquez et al,2011;Chiaramello et al, 2003a;Colloca et al,2004;Molina-Salinas et al,2010;Morales et al, 2003;Areche et al, 2009). So, some authors demonstrated that these metabolites display a wide variety of biological activities, including antimycobacterial activity (Molina-Salinas et al, 2010), trichomonicidal activity (Loyola et al, 2001), trypanocidal activity (Araya et al, 2003) and antiplasmodial activity (Loyola et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 and 2. An interesting group of bioactive metabolites, such as triterpenoids and diterpenoids with azorellane and mulinane skeletons have been obtained from Azorella, and Mulinum genera (Borquez et al,2011;Chiaramello et al, 2003a;Colloca et al,2004;Molina-Salinas et al,2010;Morales et al, 2003;Areche et al, 2009). So, some authors demonstrated that these metabolites display a wide variety of biological activities, including antimycobacterial activity (Molina-Salinas et al, 2010), trichomonicidal activity (Loyola et al, 2001), trypanocidal activity (Araya et al, 2003) and antiplasmodial activity (Loyola et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…In spite of this fact, a new chalcone was recently reported 4 , and three known sesquiterpenes have been also isolated, among them spathulenol an outstanding compound presenting a cyclopropane ring in its structure (San-Martín, A. unpublished data). This structural feature is also present in some diterpenes with azorellane 3,5 skeleton, and in a triterpene known as cycloartenol 6 . Earlier research on tribe Mulinae has led to depiction of about 30 new diterpenoids that present structural features with no evidence of synthetic or natural sources 1 .…”
Section: Introductionmentioning
confidence: 92%
“…Studies using the light petroleum extract allowed mulinane type diterpenes 2-acetoxy-mulin-11,13-diene (1), 2-acetoxy-13-hydroxymulin-11-ene (2), and the hydrolyzed derivative 2,13-dihydroxymulin-11-ene (3) to be isolated, as well as diterpenes already reported in other species of Azorella, such as mulinolic acid (4) [1a] and 13α-hydroxyazorellane (5) [8]. Finally, quercetin, 7-hydroxycoumarin and the triterpene lactone of ursolic acid (6) were isolated from the methanolic extract, which is a new finding for this species, but which has been reported in previous studies [9]. Compounds 1, 2 and 3 were evaluated as antibacterial, antioxidant and cholinesterase inhibitors.…”
mentioning
confidence: 89%